About routes and protagonists - Iguíñiz Echeverría, Javier (1994)
In this special anniversary edition of Allpanchis Phuturinqa, our land will be reborn, we have brought together studies, experiences and views of the future that point to the generation of national development proposals taking into account the Peruvian highlands as a central character. Obviously, this is neither the first attempt to do it, nor the best, nor the last.